Sleep duration, sleep quality and physical activity, but not sedentary behaviour, are associated with positive mental health in a multi-ethnic asian population: A cross-sectional evaluation - Vaingankar, J.A. (MDPI AG, 2021)
10.3390/ijerph17228489